Analisis Numerik Simulasi Kinerja Sistem Tata Udara Unitary Menggunakan Liquid-Suction Heat Exchanger dengan Refrigeran Hidrokarbon - Nuriyadi Muhammad (Jurnal Engine: Energi, Manufaktur, dan Material, 2018)
One of the environmental issues to be addressed, particularly in the field of refrigeration and air conditioning, is the destruction of the ozone layer and the effects of global warming due to the use of environmentally inefficient refrigerants. In the field of Refrigeration and Air Conditioning, refrigerant as a cooling medium, plays an important role, and until now there is still the use of refrigerant materials that are not environmentally friendly, generally synthetic refrigerant. One alternative refrigerant replacement against the synthetic refrigerant is hydrocarbon refrigerant (HC). On the other hand, several ways can improve the performance of refrigeration system by lowering the temperature of liquid line using liquid to suction heat exchanger. In this study, a numerical simulation was conducted to examine the effect of using liquid to suction heat exchanger on the performance of a unitary air-conditioning system using hydrocarbon refrigerant as a coolant fluid. The results are, liquid to suction heat exchanger increase refrigeration effect by raising heat exchanger effectivity, the highest increase is about 7%. But the use of LSHX also rises up the compression work by increasing heat exchanger effectivity by 19%. So the Coefficient of performance (COP) and relative capacity index decrease by 5%. Decreasing performance is higher in the unit that operates at higher temperatures.